Early data on long‐term efficacy and safety of inotersen in patients with hereditary transthyretin amyloidosis: a 2‐year update from the open‐label extension of the NEURO‐TTR trial. (29th May 2020) - Brannagan, T. H.; Wang, A. K.; Coelho, T.; Waddington Cruz, M.; Polydefkis, M. J.; Dyck, P. J.; Plante‐Bordeneuve, V.; Berk, J. L.; Barroso, F.; Merlini, G.; Conceição, I.; Hughes, S. G.; et al.
Abstract : Background and purpose: Hereditary transthyretin (hATTR) amyloidosis causes progressive polyneuropathy resulting from transthyretin (TTR) amyloid deposition throughout the body, including the peripheral nerves. The efficacy and safety of inotersen, an antisense oligonucleotide inhibitor of TTR protein production, were demonstrated in the pivotal NEURO‐TTR study in patients with hATTR polyneuropathy. Here, the long‐term efficacy and safety of inotersen are assessed in an ongoing open‐label extension (OLE) study. Methods: Patients who completed NEURO‐TTR were eligible to enroll in the OLE (NCT02175004). Efficacy assessments included the modified Neuropathy Impairment Score plus seven neurophysiological tests composite score (mNIS + 7), the Norfolk Quality of Life – Diabetic Neuropathy (Norfolk QOL‐DN) questionnaire total score and the Short‐Form 36 Health Survey (SF‐36) Physical Component Summary (PCS) score. Safety and tolerability were also assessed. Results: Overall, 97% (135/139) of patients who completed NEURO‐TTR enrolled in the OLE. Patients who received inotersen for 39 cumulative months in NEURO‐TTR and the OLE continued to show benefit; patients who switched from placebo to inotersen in the OLE demonstrated improvement or stabilization of neurological disease progression by mNIS + 7, Norfolk QOL‐DN and SF‐36 PCS. No new safety concerns were identified. There was no evidence of increased risk for grade 4 thrombocytopenia or severe renal events with increased duration of inotersen exposure. Conclusion: Inotersen slowed disease progression and reduced deterioration of quality of life in patients with hATTR polyneuropathy. Early treatment with inotersen resulted in greater long‐term disease stabilization than delayed initiation. Routine platelet and renal safety monitoring were effective; no new safety signals were observed.